If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + -13 = 9y + 13 Reorder the terms: -13 + -4y = 9y + 13 Reorder the terms: -13 + -4y = 13 + 9y Solving -13 + -4y = 13 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. -13 + -4y + -9y = 13 + 9y + -9y Combine like terms: -4y + -9y = -13y -13 + -13y = 13 + 9y + -9y Combine like terms: 9y + -9y = 0 -13 + -13y = 13 + 0 -13 + -13y = 13 Add '13' to each side of the equation. -13 + 13 + -13y = 13 + 13 Combine like terms: -13 + 13 = 0 0 + -13y = 13 + 13 -13y = 13 + 13 Combine like terms: 13 + 13 = 26 -13y = 26 Divide each side by '-13'. y = -2 Simplifying y = -2
| -3+9x=3(x+6) | | 18b=-234 | | 2x+30=12x | | 3c+c=48 | | 4q+2(-8+3q)=3 | | 8x-73=3x-13 | | 3x-7=7x-9 | | -11n=99 | | 2-5v-6v=2 | | 2-5v-6v=23 | | 12-7x=144-35x | | 42=-3(4n-2) | | -p-8p=3-6p | | -32=-2v | | -2a+5=5 | | 6(2x-9)=-102 | | -4n=-n-6 | | 7x^2-6= | | -39x+31=225 | | -12=-x-5x | | 8x+3=9+5x | | 6=14+n | | 3(5+3x)=-3(6-2x) | | 3x+14=x+24 | | -3x+1=-5x+17 | | 6=10-x | | 3(x+3)=(4+x) | | 2x+2x-1=12 | | 4Y+20=8 | | -3x+8=-2x+9 | | 10x-7= | | 2(2+2)*3= |